To solve the quadratic equation \( 4x^2 + 4x - 15 = 0 \) using the quadratic formula, we use the formula:
\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} \]
For the equation \( 4x^2 + 4x - 15 = 0 \), the coefficients are:
- \( a = 4 \)
- \( b = 4 \)
- \( c = -15 \)
- First, we calculate the discriminant \( b^2 - 4ac \):
\[ b^2 - 4ac = 4^2 - 4(4)(-15) = 16 + 240 = 256 \]
- Now, we can apply the quadratic formula:
\[ x = \frac{{-4 \pm \sqrt{256}}}{{2 \cdot 4}} \]
- Calculate \( \sqrt{256} \):
\[ \sqrt{256} = 16 \]
- Substitute back into the formula:
\[ x = \frac{{-4 \pm 16}}{{8}} \]
- Now calculate the two possible solutions:
- For the \( + \) case:
\[ x = \frac{{-4 + 16}}{{8}} = \frac{12}{8} = 1.5 \]
- For the \( - \) case:
\[ x = \frac{{-4 - 16}}{{8}} = \frac{-20}{8} = -2.5 \]
Thus, the solutions to the equation \( 4x^2 + 4x - 15 = 0 \) are:
\[ x = 1.5 \quad \text{and} \quad x = -2.5 \]
Therefore, the correct response is:
x=1.5, x=−2.5.